2014
DOI: 10.1159/000358844
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Slows IgA Nephropathy Progression in the Rat

Abstract: Background: IgA nephropathy (IgAN) is the most frequent glomerulonephritis worldwide. Different therapeutic approaches have been tested against IgAN. The present study was designed to explore the renoprotective potential of low-dose mammalian target of rapamycin (mTOR) inhibitor rapamycin in an IgAN rat model and the possible mechanism of action. Methods: After establishing an IgAN model, the rats were randomly divided into four groups: control, control with rapamycin treatment, IgAN model, and IgAN model with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…As no ddY mouse was available in China, we used the animal IgAN model in which a direct antigenic stimulus to esophageal endothelial mucosal cells activates local and migratory macrophages was based on our previous studies [28] . Data from other studies have also shown that this method can build a good stable animal model for IgAN [29,30] . IgAN was induced by continuous oral immunization with 0.1% BSA (G7516, Sigma Chemical Co., St. Louis, Mo., USA) with 6 m M HCl in tap water for 10 weeks, followed by tail intravenous injection of 1 mg BSA daily for 3 successive days.…”
Section: Animals and Experimental Designmentioning
confidence: 78%
“…As no ddY mouse was available in China, we used the animal IgAN model in which a direct antigenic stimulus to esophageal endothelial mucosal cells activates local and migratory macrophages was based on our previous studies [28] . Data from other studies have also shown that this method can build a good stable animal model for IgAN [29,30] . IgAN was induced by continuous oral immunization with 0.1% BSA (G7516, Sigma Chemical Co., St. Louis, Mo., USA) with 6 m M HCl in tap water for 10 weeks, followed by tail intravenous injection of 1 mg BSA daily for 3 successive days.…”
Section: Animals and Experimental Designmentioning
confidence: 78%
“…It was reported that the early application of the low-dose mTOR inhibitor rapamycin, at 1 mg·kg -1 ·day -1 for 6 weeks, may slow the progression of IgAN-induced renal injury in rats [24]. The underlying mechanism for the beneficial effect of rapamycin on IgAN is likely to be cell cycle-dependent, because rapamycin inhibited mesangial cell proliferation and arrested the cell cycle in the G1 phase, without affecting the expression of cyclin E and cyclin-dependent kinase [25].…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycinn, as an mTOR inhibition, has been shown to progress slowly in several kidney injury models [17,18,19,20,21,22,23] As a frequently occuring immune-mediated kidney disease in Asia, IgAN, with a series of complex pathogenesis, was a research hotspot over the past few decades. But in IgAN, the role and the level of autophagy are unclear.…”
Section: Introductionmentioning
confidence: 99%